Game Theory for Networks 2nd International ICST Conference, GameNets 2011, Shanghai, China, April 11-18, 2011, Revised Selected Papers - JAIN, RAHUL; Kannan, Rajgopal (Lecture Notes of the Institute for Computer Sciences, Social Informatics and Telecommunications Engineering, 2012)
This book constitutes the thoroughly refereed post-conference proceedings of the Second International Conference on Game Theory for Networks (GameNets 2011) held in Shanghai, China, April 16-18, 2011. The 45 revised full papers presented were carefully selected from numerous submissions and focus topics such as mechanism design, physical layer games, network mechanisms, stochastic and dynamic games, game-theoretic network models, cooperative games in networks, security games, spectrum sharing games, P2P and social networks and economics of network QoS.